PELAYANAN PERAWAT DAN KEPUASAN PASIEN DI RUANG ICCU - Biateris, Siren; Kawuryan, Uji; Puspita, Dinarwulan (Literasi Intelektual, 2024)
Background: Health services are a fundamental need of society, and patient satisfaction is an essential indicator of hospital service quality. Objective: This study aimed to analyze the relationship between nursing care services and patient satisfaction in the Intensive Cardiac Care Unit (ICCU) of Dr. Soedarso Regional General Hospital, West Kalimantan. Method: A cross-sectional design was applied with 70 respondents selected using incidental sampling. Data were collected through Likert-scale questionnaires and analyzed using the Chi-Square test. Result: The results showed that most respondents rated nursing services as good (92.9%) and were satisfied (91.4%). The p-value of 0.001 (<0.05) indicated a significant relationship between nursing care quality and patient satisfaction. Conclusion: The findings suggest that the better the quality of nursing services, the higher the patient satisfaction. Continuous training is needed to enhance nurses’ professionalism and communication skills.